Evaluasi Pembelajaran Aktivitas Kebugaran Jasmani Siswa SMK Di Kabupaten Cianjur - Fadilatul Fikri; Resty Gustiawaty; Astri Ayu Irawan (Universitas Hamzanwadi, 2026)
This study aimed to evaluate the implementation of physical fitness learning among vocational high school (SMK) students in Cianjur Regency based on the results of the Indonesian Physical Fitness Test (TKJI). The study employed a mixed-methods approach with a sequential explanatory design. The participants consisted of 159 students from three vocational high schools. Quantitative data were analyzed using descriptive statistics, while qualitative data were collected through interviews, observations, and documentation. The findings revealed that the overall physical fitness level of the students could be classified as good, with a mean TKJI score of 20.45. A total of 75.5% of the students were categorized as having a Good level of physical fitness, while the remaining 24.5% were classified as Very Good. Among the test components, the sit-up test achieved the highest average score, whereas the 1200/1000-meter run recorded the lowest average score. Qualitative findings indicated that physical education learning, participation in extracurricular sports activities, and the availability of adequate facilities and infrastructure contributed positively to students’ physical fitness levels. Cardiorespiratory endurance still requires improvement through the implementation of well-planned, structured, and sustainable aerobic training programs.